1991
DOI: 10.1021/bi00246a002
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenase side reactions of acetolactate synthase and other carbanion-forming enzymes

Abstract: Enzymes that mediate carbanion chemistry must protect their reactants from solvent and undesirable electrophiles, such as molecular oxygen. A number of enzymes that utilize carbanionic intermediates were surveyed for O2-consuming side reactions. Several of these enzymes, acetolactate synthase, pyruvate decarboxylase, class II aldolase, and glutamate decarboxylase, catalyze previously undetected oxygen-consuming reactions, while others such as class I aldolase, [(phosphoribosyl)amino]imidazole carboxylase, 6-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
115
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 16 publications
3
115
0
Order By: Relevance
“…Because of the spin-forbidden interaction of triplet oxygen with singlet-state molecules, oxygen is generally unreactive in the absence of an activating cofactor such as a transition metal or flavin, so its presence in protein active sites is usually unnoticed and inconsequential. One exception is the reduction of oxygen to superoxide by carbanions (28)(29)(30). Although alternative explanations for the mechanism of firefly luciferase have been offered (18), we propose that formation of the luciferin-AMP ester within the enzyme allows access to a resonance-stabilized carbanion that can reduce molecular dioxygen to superoxide by single-electron transfer and then react by subsequent recombination of the radical pair after spin inversion to form a peroxide (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Because of the spin-forbidden interaction of triplet oxygen with singlet-state molecules, oxygen is generally unreactive in the absence of an activating cofactor such as a transition metal or flavin, so its presence in protein active sites is usually unnoticed and inconsequential. One exception is the reduction of oxygen to superoxide by carbanions (28)(29)(30). Although alternative explanations for the mechanism of firefly luciferase have been offered (18), we propose that formation of the luciferin-AMP ester within the enzyme allows access to a resonance-stabilized carbanion that can reduce molecular dioxygen to superoxide by single-electron transfer and then react by subsequent recombination of the radical pair after spin inversion to form a peroxide (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, rate constants derived from the distribution of intermediates are net rate constants, which reflect the true forward rate constant multiplied by the fraction of the resulting enzyme form that partitions onto products as opposed to undergoing reversal (15). The decarboxylation step (kЈ 3 ) is presumably irreversible, but we know that steps 4 and 5 are reversible, because chemically synthesized AL can be converted to, e.g., peracetate (22) or phenylacetyl carbinol (ref. 23 and D.M.C., unpublished results) by AHAS II.…”
Section: Discussionmentioning
confidence: 99%
“…23 and D.M.C., unpublished results) by AHAS II. On the basis of Schloss and coworkers' observations on the peracetate-forming oxygenase reaction (22,24), one also can assume that there is reversible binding of the acceptor ketoacid to the enzyme-HEThDP complex before its reaction (as opposed to Theorell-Chance kinetics for step 4): Both pyruvate and 2-keto- butyrate can compete with oxygen for enzyme-bound HEThDP, but the competition saturates at Ͻ100% inhibition of the oxygenase reaction. Despite the difference in microscopic rate constants for ligation of ketobutyrate and pyruvate to bound HEThDP Ϫ , the slow reduction of FAD observed during substrate turnover by AHAS II is also only slightly dependent on the second substrate (14).…”
Section: Discussionmentioning
confidence: 99%
“…the release of CO # . It is of interest that Abell and Schloss [18] have demonstrated that several enzymes mediating carbanion chemistry are capable of reacting with molecular oxygen, thus catalysing oxygen-consuming side reactions. Among these enzymes, a PLP-dependent enzyme, GAD, has been shown to exhibit oxygenase activity.…”
Section: Discussionmentioning
confidence: 99%